DECAPOD INVENTORY UNVEILING SPECIES RICHNESS AN DISTRIBUTION IN THE LAMPUNG REGION, INDONESIA - Muhammad Khalid Yudhistiro; Windra Priawandiputra; Achmad Farajallah (Treubia, 2025)
Indonesia is recognized as one of the world’s centers of crab diversity, with approximately 1,400species of Brachyura and an estimated 210–300 species of Anomura. However, the data on crabdiversity is sparse and understudy in some areas. This study aims to assess the richness and distributionof crabs in Lampung region. Survey was conducted in Tanggamus, the West Coast of Lampung, andEast Lampung using purposive sampling approach. A total of 23 crab species from six families wererecorded from Lampung region. Tanggamus exhibited the highest species diversity compare to WestCoast and East Lampung. The member of family Xanthidae was frequently observed across all threeregions. Further studies are recommended to examine ecological drivers, climate change impacts, andanthropogenic pressures influencing crab distribution to support effective conservation strategies.